2015
DOI: 10.1016/j.supflu.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of macroporous alginate-based aerogels for biomedical applications

Abstract: Highlights • alginate-starch Ca-crosslinked aerogels by CO 2 induced gelation and sc-drying; • macroporosity due to CO 2 expansion and intrinsically high mesoporosity; • alginate-starch aerogels are bioactive and non-cytotoxic. ABSTRACT Aerogels are a special class of ultra-light porous materials with growing interest in biomedical applications due to their open pore structure and high surface area. However, they usually lack macroporosity, while mesoporosity is typically high. In this work, carbon dioxide ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 45 publications
2
87
2
Order By: Relevance
“…Fast depressurization can lead to increased macroporosity of the gels. This phenomena can be applied for tissue engineering applications where macroporosity of the material with interconnectivity is an important feature for the growth and proliferation of cells 13,14 . In addition, the crosslinking degree in Protocol Section 1 plays an important role in the syneresis and swelling property of the amidated pectin hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…Fast depressurization can lead to increased macroporosity of the gels. This phenomena can be applied for tissue engineering applications where macroporosity of the material with interconnectivity is an important feature for the growth and proliferation of cells 13,14 . In addition, the crosslinking degree in Protocol Section 1 plays an important role in the syneresis and swelling property of the amidated pectin hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…Straight sol-gel gelling induced by compressed CO 2 has only been described for polymeric aerogelsi nvolving highly reactive monomers, such as silsesquioxanes, [35] and some biopolymers. [36][37][38][39] In the developed supercritical CO 2 procedure, the mechanism of gelling and drying was visually followed through the sapphire windowso ft he high-pressure reactor,w hich allow the acquisition of optical pictures ( Figure 4).…”
Section: Gellinga Nd Drying Mechanism In Sccomentioning
confidence: 99%
“…Nowadays, there has been considerable interest in carbon-based nanomaterials to fabricate a new class of materials with unique properties [20]. In this study, a method to improve the mechanical and biological properties of the scaffold by the incorporation of alginate and GO was used, since it has been previously reported as successful [6,28,[35][36][37]. Even though it has been established that both materials could be employed to improve general properties of biomaterials, results in this study showed that the incorporation of GO could negatively affect cell attachment, proliferation, and response.…”
Section: Discussionmentioning
confidence: 99%
“…Baldino et al [36] also confirmed that the supercritical process does not modify the gel organization and avoids gel collapse during drying. Martins et al [35] reported an alginate-based aerogel for TE; to obtain an adequate porosity in the structure, Martins et al proposed different pressuring and depressurizing rates. In this study, a collagen-alginate-GO aerogel with a highly porous structure is presented; the incorporation of collagen type I and the crosslinking performed by UV light allow a porous three-dimensional structure to be formed, even without the use of specific pressuring and depressurizing rates; also, the biological characteristics of collagen added to the aerogel provide adequate properties for its use in TE.…”
Section: Discussionmentioning
confidence: 99%